Digital Education in the Nigerian Economy, 1999 2022 - Ongele, Festus Nwankwo (Jurnal Ilmu Sosiologi Dialektika Kontemporer, 2024)
The study consciously examined the impact of digital education on the Nigerian economy from 1999 to 2022. It investigated how digital education has transformed the educational landscape, influenced economic growth, and affected the workforce. It was however, discovered that digital education has increased access to quality education, especially in rural areas. To that effect, it improved economic growth by enhancing human capital development and productivity. It has equally transformed the workforce, with increased demand for digital skills. It enabled innovation in the sector of education and provided the need to invest more in the digital infrastructure.  It further revealed that private-public partnership is required to promote both the digital education and economic growth and development in the country. Primary and secondary sources were relied on while its data were analyzed qualitatively, using content analysis and thematic approaches.